Peramalam Ekspor Minyak Kelapa Sawit Indonesia Menggunakan Model ARIMA - Rakhmawan, Sapto (Universitas Islam Negeri Alauddin Makassar, 2019)
Indonesia is a country known as the biggest exporter of palm oil in the world. It is well known that palm oil is very important for our daily life including cooking oil, vegetable fat for milk and ice cream, raw materials of soap or cosmetics industry, or alternative fuels. The export value of palm oil has contributed significantly to the trade balance of Indonesia, and hence it is essential for boosting the economic development of the nation. Forecasting the export values of palm oil, therefore, becomes a necessity to help the government in making right policy related to the economic development. In this article, we discussed ARIMA model and applied these model to forecast the palm oil export values. We used monthly palm oil export value starting from January 2008 until December 2018. The results showed that ARIMA model was suitable for time series data. The forecasting results showed that the palm oil export value will increase for the next 24 period.